PHARMACOGNOSTIC, PHYSICOCHEMICAL AND PHYTOCHEMICAL STUDIES OF SEBASTIANIA CHAMAELEA (L).MUELL.ARG - Anjali Asok*; Mahesh C.D; Shiva Manjunatha M.P; Seema Pradeep (AYUSHDHARA, 2018)
Background: The plant Sebastiania chamaelea (L).Muell.arg belongs to Euphorbiaceae family and is a native to Africa, southern Asia and Australia. This is used as a folk medicine for the management of pain in various parts of the world. Very few studies have been conducted on the S.chamaelea. This present study was conducted to establish quality control parameters of the plant. Methodology: The study deals with detailed macro morphology, microscopy of transverse section of root, stem, leaves and fruit. The powder microscopy of seeds was carried out as well. The other parameters like physicochemical constants and phytochemical screening were studied using the standard protocol. Results: The study provides referential information for the correct identification and standardization of crude drug of Sebastiania chamaelea (L).Muell.arg.